Media jako forma przedstawień zbiorowych polityki i jej teoriopoznawcze uwarunkowania - Kowalczyk, Ryszard (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
The paper touches upon the issue of media behavior in the market of public communication and the epistemological determinants of the process of media imaging of political reality. Consequently, it becomes feasible to distinguish two types ofmessages: one focused on information and the other concentrated on overt or covert persuasion. Thus, the author emphasizes the ritual function of the media, which meets the needs of average recipients as well as those of commercialized media. Therefore a certain interaction ritual of the media that takes place between them and their audience points to the media as entities dynamically responding to changing circumstances and aware of their own potential to create reality.